Dunia Simbolik Penyandang Disabilitas Netra Melalui Tindakan Komunikatif di Ruang Publik Digital - Serepina Tiur Maida (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This study aims to analyze the symbolic world of visually impaired persons through communicative action in the digital public sphere. The research employed a qualitative narrative approach within an interpretive paradigm. Data were obtained from YouTube videos in 2025 featuring narratives of visually impaired individuals in Indonesia. Data collection techniques included digital observation, video transcript documentation, and content literature review. Data analysis applied the Miles and Huberman model integrated with Berger and Luckmann’s symbolic world theory and Habermas’s communicative action theory. The findings reveal that the digital public sphere has become a symbolic arena for visually impaired persons to construct social identity, seek recognition, and represent life experiences through symbols of struggle, hope, spirituality, and social dedication. Communicative actions presented in the video narratives were inspirational, religious, educational, and motivational, fostering empathy and inclusive awareness within society. This study confirms that digital communication functions not only as a medium of information exchange but also as a space for social meaning production and symbolic struggle for visually impaired communities in achieving equality within the digital public sphere.